La modélisation : un outil pour la gestion et l'aménagement en forêt. - Françiois Goreaud; F. de Coligny; Benoit Courbaud; JF. Dhôte; Ph. Dreyfus; Thomas Pérot (VertigO)
In order to predict the evolution of forest stands, and thus to facilitate forest management, researchers have developed different types of models of stand dynamics. In this paper, we illustrate the interest of such models as management tools. We consider three applications : (i) in a pure, even-aged oak stand, the use of a model in order to take into account the effect of productivity changes on growth ; (ii) in mixed, uneven-aged stands of spruce and fir, the comparison through simulation of a classical thinning to a thinning with openings ; (iii) in large-scale areas, the modelling of the dynamics of species composition of mixed stands. We finally discuss the limitations of models and future perspectives for research in this field.